Factors involved in the progress of preclinical atherosclerosis associated with systemic lupus erythematosus: a 2-year longitudinal study. Issue 6 (16th August 2009) - Rua-Figueroa, I; Arencibia-Mireles, O; Elvira, M; Erausquin, C; Ojeda, S; Francisco, F; Naranjo, A; Rodríguez-Gallego, C; Garcia-Laorden, I; Rodríguez-Perez, J; Rodríguez-Lozano, C
Abstract : Objectives: To assess the changes in carotid intima-media thickness (IMT) and the associated risks factors in patients with low severity systemic lupus erythematosus (SLE). Methods: Common carotid IMT measurements were obtained by ultrasound from 101 patients with SLE at an interval of 2 years. Cardiovascular risk factors, disease activity, accumulated damage, severity (Katz index) and biochemical parameters (including high sensitivity C-reactive protein, interleukin 6, C3a, C4a, C5a and homocysteine) were also assessed. Multiple linear regression was used to assess the effect of these variables on the end IMT measurement (eIMT) adjusted to the baseline measurement (bIMT). Results: The cohort comprised 94.1% women, with a mean age at entry of 41.5 years and a mean disease duration of 12.1 years. An increase of 0.078 mm in IMT was detected over 2 years, from a mean bIMT of 0.37 mm to a mean eIMT of 0.44 mm (p<0.001). When adjusted for the bIMT, multiple linear regression identified bIMT, age at diagnosis, homocysteine, C3 and C5a as risk factors for IMT progression. Conclusions: IMT significantly increases over 2 years in patients with SLE. Age, baseline IMT, C3, C5a anaphylatoxin and homocysteine are all associated risk factors, supporting a role for complement and homocysteine in the early stages of premature SLE-associated atherosclerosis.